PENGGUNAAN UPAH BAYANGAN UNTUK MEMPERKIRAKAN PENAWARAN TENAGA KERJA USAHATANI Kasus Pada Usahatani Ubikayu di Kabupaten Banyumas - WIDYARINI, INDAH; SUBAGYO, SARDJU (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 7, No. 3 November 2007, 2012)
Shadow wages can be used for estimation labor supply of farm household with Cobb- Douglas production function. The research conducted in five villages, i.e., Pageraji, Pejogol, Cilongok, Pernasidi, and Cikidang in Banyumas Regency. The respondents were chosen by Cluster Random Sampling. The research result showed that the shadow wages as a supply function of cassava farm in dry land were flatter then in paddy land. The more shadow wages the more labor supply.
Keywords: Shadow Wages, Supply Labor.